Penggunaan Instagram sebagai Media Literasi Digital pada Akun @dp3akarawang. - Sabrina Nurfauziyah; Siti Nursanti; Wahyu Utamidewi (Peneliti.net, 2023)
Digital communication technology is always developing and thus, creates new communication and information media. One of the products of digital communication technology development is social media. Social media has many functions, one of which is the function as a medium for digital literacy. The Instagram account @dp3akarawang is an account managed by DP3A (Dinas Pemberdayaan Perempuan dan Perlindungan Anak) Kabupaten Karawang. DP3A Kabupaten Karawang’s Instagram account uploads publications of their activity and some educational content. This study aims to analyze the @dp3akarawang account as a digital literacy medium and use the interview method with the @dp3akarawang account’s admin as the informant. The results obtained are that in running accounts and creating content, the admin has succeeded in implementing five of the eight essential elements of digital literacy, those elements are cognitive, constructivist, creative, communicative, and civic elements. Keywords: digital literacy; social media; Instagram; account @dp3akarawang